Investigation of parents’ perceptions of sending their children to swimming courses in terms of various variables - Ejder GUNES (BMC Sports Science, Medicine and Rehabilitation)
Abstract The study aims to investigate parent’s perceptions regarding their children’s participation in swimming courses, considering various variables. Within the scope of the study, the “Reasons for Parents Sending Their Children to Swimming Sports Scale,” consisting of 21 questions, was utilized. This Scale evaluates three sub-factors: the motivations behind parents sending their children to swimming sports, the impact of swimming sports on their children, and the level of satisfaction with swimming sports. These factors were then compared with the parents’ demographic data. The sample group comprised parents of children participating in different swimming courses in Ankara and those attending courses organized by the Presidential Guard Regiment Command. Data analysis has clarified factors influencing children’s participation in swimming courses and highlighted key dimensions of parental perceptions. The findings indicate that equipping children with swimming skills can mitigate the risk of drowning and substantially enhance their physical activity levels. In this context, our research has identified a strong correlation between parent’s physical activity levels and their children’s. This finding highlights the critical role of parents in encouraging physical activity and underscores the importance of parent’s serving as role models for their children.